New insights into North Sea deep crustal structure and extension from transdimensional ambient noise tomography. Issue 2 (10th October 2020) - Crowder, E; Rawlinson, N; Cornwell, D G; Sammarco, C; Galetti, E; Curtis, A
SUMMARY: The deep crustal structure beneath the North Sea is poorly understood since it is constrained by only a few seismic reflection and refraction profiles. However, it is widely acknowledged that the mid to lower crust plays important roles in rift initiation and evolution, particularly when large-scale sutures and/or terrane boundaries are present, since these inherited features can focus strain or act as inhibitors to extensional deformation. Ancient tectonic features are known to exist beneath the iconic failed rift system of the North Sea, making it an ideal location to investigate the complex interplay between pre-existing regional heterogeneity and rifting. To this end, we produce a 3-D shear wave velocity model from transdimensional ambient seismic noise tomography to constrain crustal properties to ∼30 km depth beneath the North Sea and its surrounding landmasses. Major North Sea sedimentary basins appear as low shear wave velocity zones that are a good match to published sediment thickness maps. We constrain relatively thin crust (13–18 km) beneath the Central Graben depocentres that contrasts with crust elsewhere at least 25–30 km thick. Significant variations in crustal structure and rift symmetry are identified along the failed rift system that appears to be related to the locations of Laurentia–Avalonia–Baltica palaeoplate boundaries. We constrain first-order differences in structure between palaeoplates; with strong lateral gradients in crustal velocity related to Laurentia–Avalonia–Baltica plate juxtaposition and reduced lower crustal velocities in the vicinity of the Thor suture, possibly representing the remnants of a Caledonian accretionary complex. Our results provide fresh insight into the pivotal roles that ancient terranes can play in the formation and failure of continental rifts and may help explain the characteristics of other similar continental rifts globally.